Formulasi Sediaan Eyeshadow Ekstrak Air Buah Syzygium cumini dalam Bentuk Compact Powder - Dwiwulandari, Fransisca Yunita; Darsono, Farida Lanawati; Wijaya, Sumi (Faculty of Pharmacy, Widya Mandala Surabaya Catholic University, Indonesia, 2018)
Coloring substance are needed in eyeshadow. It is used to give colors, shadows, and glittery effect on eyes. The trend in beauty world nowadays is using a natural dye because of safety issues. Antocyanine, which is contained in “juwet” fruit (Syzygium cumini), is one of the potential natural dyes. The aim of this research is to know the effect of Syzygium cumini in different concentration (20%, 25% dan 30%) on the physical quality and ffectiveness of the eyeshadow. The extract of Syzygium cumini fruit was formulated into compact powder eyeshadow. This type of preparation is the dominant dosage form used because it has good adhesiveness to the skin. The extract was obtained by extracting the juice and evaporated it using thermostatic water bath in the temperature of 40-60°C. The result showed that the increase in extract concentration significantly affected the physical quality test results (organoleptic, pH, particle size, friability and hardness), but did not affect the color dispersion and effectiveness. Based on the evaluation, formula II (extract of Syzyium cumini 25 %) was chosen as the best formula.